2004
DOI: 10.1161/01.str.0000129790.00318.a3
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin and Osteopontin Are Expressed at High Concentrations Within Symptomatic Carotid Atherosclerosis

Abstract: OPG and OPN are upregulated in symptomatic human carotid atherosclerosis with possible implications for plaque stability. Angiotensin II blockade is able to downregulate OPG secretion in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
184
1
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 213 publications
(200 citation statements)
references
References 43 publications
(46 reference statements)
6
184
1
9
Order By: Relevance
“…First, most high‐risk individuals received (multi‐)drug treatment. It has been demonstrated that in vivo treatment with antidiabetic medication,43, 44, 45, 46 statins,47, 48 heparins,49, 50 or glucocorticoids51 and in vitro treatment with irbesartan52 or different immunosuppressive therapies53 affect circulating osteoprotegerin levels. Second, circulating osteoprotegerin levels differ in people with preexisting diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, most high‐risk individuals received (multi‐)drug treatment. It has been demonstrated that in vivo treatment with antidiabetic medication,43, 44, 45, 46 statins,47, 48 heparins,49, 50 or glucocorticoids51 and in vitro treatment with irbesartan52 or different immunosuppressive therapies53 affect circulating osteoprotegerin levels. Second, circulating osteoprotegerin levels differ in people with preexisting diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it promotes vascular medial fibrosis76 and may exert indirect proatherosclerotic effects by blocking TNF‐related apoptosis‐inducing ligand 77. Atherosclerotic plaques that highly express osteoprotegerin exhibit more calcification,8 but studies yielded conflicting results about its relevance to plaque stability and conversion to a symptomatic plaque 52, 73, 78, 79. These inconsistent reports emphasize the wide‐ranging aspects of osteoprotegerin in the complexity of regulatory processes in atherogenesis and call for more experimental studies to improve our understanding of this pathway in human disease.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria included: a) patients with amaurosis fugax alone, non-focal, atypical or distant neurological symptoms, b) asymptomatic patients, c) patients not receiving a Statin or anti-platelet medication. Clinical, imaging and serum characteristics of the patients were prospectively measured and recorded as previously described [19,20].…”
Section: Patientsmentioning
confidence: 99%
“…A conventional endarterectomy was performed and specimens were immediately placed in cold culture medium and brought to the laboratory for experimental work [19]. Specimens were dissected into the proximal internal carotid (PIC) and common carotid (CC) endarterectomy sites for primary assessment by immunohistochemistry (4 patients, 4 biopsies) or explant culture (20 patients for each drug treatment; 10 assessed by Western blotting and 10 for TM activity).…”
Section: Specimensmentioning
confidence: 99%
See 1 more Smart Citation